Orlando Gatica Studio - Gatica Ayala, Orlando (Base Diseño e Innovación, 2014)
This is a company oriented to design, fabrication and exportation of special furniture with their own design line, as well as to face projects related to equipment and interiors, working with a multidisciplinary team of architects, designers, engineers and others.Orlando Gatica Studio has dedicated to impose a work style for over 17 years, the constant innovation, the sustained improvements on product quality and design, have taken this company to work in more than 3.000 projects for big companies, homes and line productions branded O. This brand has a constantly renewing collection, focused on having a local designing identity and the use of local raw materials, in search of pure and elegant objects, worthy of worldwide recognition.